USAGE OF DISCOURSE ANALYSIS IN VARIOUS DISCIPLINE. ("Conference on Universal Science Research 2023", 2023)
Language is a social phenomenon. The mother tongue of every nation living in the territory of the Republic of Uzbekistan is a bright indicator of its national identity and spiritual culture. Language forms the mind in conjunction with thought. The connection between speech and thinking is manifested not only at the deep stages of psychological processing, but also at the level of social phenomena. The influence of words on a person and his behavior is well known to everyone. "Although language and thinking cannot live without each other, they do not represent the same phenomenon. This article provides information on the use of speech analysis in various disciplines.